Low-Power In-Circuit testing of a LNA - José Machado da Silva (2005)
A new technique is proposed to tackle in-circuit testing of embedded RF blocks. It relies on observing the cross-correlation between its output voltage and power supply current, using a translinear cross-correlator circuit. Although a structural test is performed, simulation results show that fault detection criteria can be established based on acceptable deviations of performance characterization parameters. The case of a Low Noise Amplifier is presented.